Nanostructure coating as well as preparation method and application thereof

By designing specific periodic coating units in nanomultilayer coatings, the trade-off between nanolayer thickness and performance is solved, and the high hardness, toughness and long life of nanostructured coatings in cutting tools are achieved.

CN119663182APending Publication Date: 2025-03-21XIAMEN TUNGSTEN CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411895800.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the structural design of existing nano multilayer coatings, the problem of choice between the thickness of the nanolayer, the hardness and binding force, and it is difficult to have high hardness and strong toughness at the same time.

Method used

By designing a specific periodic coating unit, including at least 3 composite structural layers, the thickness of the first component layer and the second component layer have a large difference and meets a specific thickness ratio range to achieve superhardness of the thin period and toughness of the thick period.

Benefits of technology

The nanostructured coating is achieved to significantly improve service life in cutting tool applications, while maintaining high binding force.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663182A_ABST
    Figure CN119663182A_ABST
Patent Text Reader

Abstract

The invention relates to a nano-structure coating as well as a preparation method and application thereof. The nano-structure coating comprises periodic coating units which are sequentially stacked, the periodic coating unit comprises at least three composite structure layers; the composite structure layer comprises a first component layer and a second component layer; in each composite structure layer, the thicknesses of the first component layers are completely different or not completely the same; and in each composite structure layer, the thicknesses of the second component layers are completely different or not completely the same. According to the nano-structure coating provided by the invention, through the specific periodic coating units, the nano-structure coating has ultra-hardness of a thin period and obdurability of a thick period at the same time, and when the nano-structure coating is applied to the cutting tool, the service life of the cutting tool can be remarkably prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of coatings and relates to a structural coating, in particular to a nanostructured coating and a preparation method and application thereof. Background Art

[0002] With the development of cutting tool technology, people have put forward higher and higher requirements on the materials and performance of cutting tools, and need to obtain cutting tools with high hardness, high wear resistance, high toughness and high precision. Depositing coatings on the surface of cutting tools through physical vapor deposition (PVD), chemical vapor deposition (CVD) and other technologies has become an important direction for the development of modern cutting tools. As an important component of cemented carbide cutting tools, coatings are closely related to the performance of cutting tools together with substrates and grooves. Stable coatings can significantly improve the service life and processing efficiency of cutting tools.

[0003] TiAlN coating can improve the cutting performance and service life of the tool. With the development of PVD technology, the coating continues to go deeper from a single layer to a multilayer, nanostructure, etc., and nanocomposite coatings with higher hardness, stronger wear resistance, and special nanostructures are invented and paid attention to. For example, the existing more commonly used TiAlMeN-TiAlN nano multilayer coating is a coating system composed of nanolayers of two different materials and structures such as TiAlMeN and TiAlN with nanoscale. The coating has a periodicity of nanometer scale in the thickness direction and has a basically fixed superlattice period of a double-layer thickness. Compared with single-layer and multilayer structure coatings, due to the Hall-Petch relationship caused by the nanoscale in the structure, it shows superhardness and supermodulus effect in mechanical properties, has superhardness that other coatings do not have, and can improve wear resistance.

[0004] Most existing nano-multilayer coatings are single-period, which means that the thickness and thickness relationship between the two nano-layers of different materials and / or structures are usually constant in the same coating. Under the same composition process, when the thickness of the nano-layer is thinner, it will bring smaller nano-scale grains to the coating, and according to the Hall-Page relationship, it will show stronger superhard effect and wear resistance; but thinner nano-thickness also means that in the coating structure of the same thickness, the number and density of interfaces between the nano-layers are also higher. Due to the interfaces between different nano-layers, the lattice structure, lattice constant, etc. usually change too quickly and frequently, which significantly increases the internal stress between the coatings, making the coatings on the interface insufficient in bonding strength and poor in toughness. In actual applications, they are easy to fall off under high temperature and high impact.

[0005] Therefore, under the same other conditions, when the nanometer thickness of the single-period nano multilayer coating is thin and the period is short, the coating exhibits high hardness and high wear resistance in application, but the bonding force is insufficient and easy to peel off. When the nanometer thickness is thick and the period is long, the coating exhibits good bonding force and is not easy to peel off in application, but the hardness and wear resistance are reduced. In coating design and application, it faces the trade-off problem between the thickness of the nanolayer in structure and the hardness and bonding force of the coating in performance.

[0006] Therefore, how to design a nanostructured coating so that it has a sufficiently thin nano-thickness layer to provide high hardness and high wear resistance, and has a sufficiently small interface between coatings to provide bonding strength is a technical problem that urgently needs to be solved in this field. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a nanostructured coating and a preparation method and application thereof. The nanostructured coating has a specific periodic coating unit so that the nanostructured coating has both ultra-hardness in thin periods and toughness in thick periods. When applied to cutting tools, the service life of the cutting tools can be significantly improved.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In the first aspect, the present invention provides a nanostructured coating, which comprises periodic coating units stacked in sequence; the periodic coating units comprise at least three composite structure layers; the composite structure layers comprise a first component layer and a second component layer; in at least one composite structure layer, the thickness of the first component layer is greater than the thickness of the second component layer; in at least one composite structure layer, the thickness of the second component layer is greater than the thickness of the first component layer; in each of the composite structure layers of a single periodic coating unit, the thickness of the first component layer is completely different or not completely the same, and the thickness of the second component layer is completely different or not completely the same.

[0010] In the periodic coating unit, the thickness of the thickest first component layer is a max The thickness of the thinnest first component layer is a min The thickness of the second component layer is b. max The thickness of the thinnest second component layer is b min , the unit of thickness of each layer is nm; in the periodic coating unit, the thickness of each layer satisfies: 1.5≤a max / a min ≤3, 1.5≤b max / b min ≤3,1.5≤a max / b min ≤3, 1.5≤b max / a min ≤3.

[0011] The nanostructured coating provided by the present invention has both ultra-hardness in thin periods and toughness in thick periods through specific periodic coating units. When applied to cutting tools, the service life of the cutting tools can be significantly improved.

[0012] Specifically, the thickness of the first component layer of the existing single-period nanostructure coating is a nm, the thickness of the second component layer is b nm, and the thickness of the single-period layer is c = (a + b) nm. The number of nanolayer interfaces per unit thickness (taking 1 μm = 1000 nm as an example) is 1000 / c, which is also a constant. Among them, the size of a and b affects the hardness and wear resistance of the coating, and the size of the number of nanolayer interfaces per unit thickness 1000 / c affects the bonding strength of the coating.

[0013] In a single periodic coating unit of the nanostructured coating of the present invention, the thickness of the first component layer and the thickness of the second component layer are not constant, there are at least 3 layers of composite structure layers, the thickness of the first component layer in at least 1 layer of composite structure layer is greater than the thickness of the second component layer, and the thickness of the second component layer in at least 1 layer of composite structure layer is greater than the thickness of the first component layer. When the thickness of the composite structure layer is the same, the number of nanolayer interfaces per unit thickness is still 1000 / c. When the number and density of nanointerfaces, i.e., the difference in the bonding force of the coating, a thinner thickness relative to the single-period nanolayer can be obtained. Based on the Hall-Petch relationship, a thinner thickness can improve the hardness, and the first component layer with the thinnest thickness and the second component layer with the thinnest thickness can significantly improve the overall hardness of the nanostructured coating. Therefore, compared to the single-period nanostructured coating, the nanostructured coating provided by the present invention can significantly improve the hardness when the bonding force difference is not large.

[0014] In order to ensure that the nanostructured coating has a significant improvement in hardness without much difference in bonding strength, a min with a max , and b min With b max There is enough difference. When the thickness of each layer of the periodic coating unit satisfies a max / a min ≥1.5, b max / b min ≥1.5, a max / b min ≥1.5 and b max / a min≥1.5, the hardness improvement provided by the first component layer with the smallest thickness and the second component layer with the smallest thickness can be significantly greater than the hardness attenuation caused by the first component layer with the thickest thickness and the second component layer, which significantly improves the overall hardness of the coating; but when the thickness difference is too large, the microstructures such as the phase composition and lattice constant of the second component layer with the smallest thickness will tend to grow epitaxially on the basis of the first component layer with the largest thickness, causing the lattice distortion of the thinnest second component layer, from the lattice constant of the second component to the lattice constant of the first component. Although this can improve the hardness of the nanostructured coating, it will cause the nanostructured coating's resistance to plastic deformation to decline, which will lead to a significant reduction in the bonding force of the nanostructured coating. Therefore, it is necessary to make the thickness of each layer in the periodic coating unit satisfy: 1.5≤a max / a min ≤3, 1.5≤b max / b min ≤3,1.5≤a max / b min ≤3, 1.5≤b max / a min ≤3.

[0015] Among them, 1.5≤a max / a min ≤3, for example, it can be 1.5, 1.8, 2, 2.4, 2.5, 2.8 or 3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] 1.5≤b max / b min ≤3, for example, it can be 1.5, 1.8, 2, 2.4, 2.5, 2.8 or 3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0017] 1.5≤a max / b min ≤3, for example, it can be 1.5, 1.8, 2, 2.4, 2.5, 2.8 or 3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] 1.5≤b max / a min ≤3, for example, it can be 1.5, 1.8, 2, 2.4, 2.5, 2.8 or 3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] When there are too many layers of composite structure layers, when there are multiple continuous composite structure layers with a first component layer thickness greater than the second component layer thickness, the microstructures such as the phase composition and lattice constant of the second component layer inside the composite structure layer tend to grow epitaxially on the basis of the first component layer, causing the second component layer to undergo lattice distortion, from the lattice constant of the second component layer to the lattice constant of the first component layer. When there are multiple continuous composite structure layers with a first component layer thickness less than the second component layer thickness, there is a lattice constant of the first component layer that is distorted to the lattice constant of the second component layer; both of these situations will lead to a decline in the ability of the nanostructured coating to resist plastic deformation, resulting in a significant reduction in bonding strength.

[0020] Therefore, as a preferred technical solution, the periodic coating unit includes 3 to 10 composite structure layers, for example, it can be 3 layers, 4 layers, 5 layers, 6 layers, 7 layers, 8 layers, 9 layers or 10 layers, but is not limited to the listed values, and the remaining unlisted values ​​within the numerical range are also applicable.

[0021] Preferably, the thickness of the first component layer is 4nm-70nm, for example, 4nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm or 70nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the thickness of the second component layer is 4nm-70nm, for example, 4nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm or 70nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] When the thickness of the composite structure layer or a single periodic coating unit is too thin, the number of nano-layer interfaces per unit thickness is too large, and the bonding force of the coating is poor; and when the thickness of the composite structure layer or a single periodic coating unit is too thick, the hardness of the coating decreases. Therefore, it is necessary to optimize the thickness of the composite structure layer and the single periodic coating unit.

[0024] Preferably, the thickness of the composite structure layer is 12nm-100nm, for example, it can be 12nm, 15nm, 20nm, 30nm, 40nm, 50nm, 60nm, 80nm or 100nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] Preferably, the thickness of the periodic coating unit is 36nm-1000nm, for example, it can be 36nm, 50nm, 100nm, 300nm, 400nm, 500nm, 600nm, 800nm ​​or 1000nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] In the present invention, the first component in the first component layer and the second component in the second component layer is different from the second component.

[0027] Preferably, the first component of the first component layer is M1 a M2 b M3 c M m .

[0028] M1 includes any one of Ti, Cr, Zr, Hf, W or Mo.

[0029] M2 includes Al.

[0030] M3 includes any one of Ti, Cr, Zr, Hf, V, Ta, Nb, W, Mn, Mo or Si, or a combination of at least two of them. Typical but non-limiting combinations include a combination of Ti and Cr, a combination of Zr and Hf, a combination of V and Ta, a combination of Nb and W, a combination of Ti, Cr, Zr and Hf, a combination of Ta, Nb, W, Mn, Mo and Si, or a combination of Ti, Cr, Zr, Hf, V, Ta, Nb, W, Mn, Mo and Si.

[0031] M is any one of N, O, C or B or a combination of at least two thereof. Typical but non-limiting combinations include a combination of N and C, a combination of N and B, a combination of C and B, or a combination of N, C and B.

[0032] a>0.3, b>0.3 or b=0, c≤0.2, and a+b+c=1; when M is N and / or C, 0.95≤m≤1.05; when M is O, 1.45≤m≤1.55; when M is B, 1.95≤m≤2.05.

[0033] Preferably, the second component in the second component layer is N1 x N2 y N3 z Q q .

[0034] N1 includes any one of Ti, Cr, Zr, Hf, W or Mo.

[0035] N2 includes Al.

[0036] N3 includes any one of Ti, Cr, Zr, Hf, V, Ta, Nb, W, Mn, Mo or Si, or a combination of at least two of them. Typical but non-limiting combinations include a combination of Ti and Cr, a combination of Zr and Hf, a combination of V and Ta, a combination of Nb and W, a combination of Ti, Cr, Zr and Hf, a combination of Ta, Nb, W, Mn, Mo and Si, or a combination of Ti, Cr, Zr, Hf, V, Ta, Nb, W, Mn, Mo and Si.

[0037] Q is any one of N, O, C or B or a combination of at least two thereof. Typical but non-limiting combinations include a combination of N and C, a combination of N and B, a combination of C and B, or a combination of N, C and B.

[0038] And x>0.3, y>0.3 or y=0, z≤0.2, and x+y+z=1; when Q is N and / or C, 0.95≤q≤1.05, when Q is O; 1.45≤q≤1.55, when Q is B, 1.95≤q≤2.05.

[0039] M1 and N1 are the main elements, which are conducive to forming the main phase components and microstructures of the dual-periodic nanostructure coating. Exemplarily, when M and Q are independently nitrogen, when M1 and N1 are both Ti, the first component thick layer, the second component thin layer, the first component thin layer and the second component thick layer are all TiN coatings (such as TiAlN, TiSiN, etc.), which have the characteristics of high hardness; when M is Ti and Q is Mo, the first component thick layer and the first component thin layer are TiN coatings, which have the characteristics of high hardness and wear resistance; the second component thin layer and the second component thick layer are MoN coatings, which have the effects of improving lubrication, reducing cutting force and improving cutting conditions.

[0040] M2 and N2 elements are the main strengthening elements, and Al can alloy and strengthen the coating, thereby improving the performance of the coating.

[0041] M3 and N3 are secondary strengthening elements that can further improve the cutting performance of the coating under specific working conditions. For example, Ta and Nb can reduce the hardness attenuation at high temperatures and are suitable for dry cutting without coolant; Si can form nanocrystals, while V and Cr can further refine the coating grains and improve the hardness of the coating by hindering the epitaxial growth of the coating.

[0042] In a second aspect, the present invention provides a method for preparing a nanostructured coating, the preparation method comprising the following steps:

[0043] The periodic coating units are sequentially deposited on the surface of the substrate by a physical vapor deposition method to obtain the nanostructured coating described in the first aspect.

[0044] Preferably, the physical vapor deposition device used in the physical vapor deposition comprises:

[0045] A rotating disk is used to fix the substrate; a first component target material and a second component target material are evenly placed around the rotating disk; a sputtering surface of the first component target material and a sputtering surface of the second component target material are respectively facing the surface to be coated of the substrate, and baffles capable of controlling the opening and closing size are independently arranged between the first component target material and the rotating disk, and between the second component target material and the rotating disk.

[0046] Preferably, the physical vapor deposition includes: fixing the substrate on a rotating disk, heating it to the process temperature under vacuum conditions, introducing argon gas for etching, and then introducing argon gas and / or reaction gas for coating deposition; when the surface to be coated of the substrate faces the first component target, the surface atoms of the first target are ionized under the action of high temperature and electric arc, and the ions move toward the surface to be coated of the substrate under the action of negative bias voltage to form a first component layer; when the surface to be coated of the substrate faces the second component target, the surface atoms of the second target are ionized under the action of high temperature and electric arc, and the ions move toward the surface to be coated of the substrate under the action of negative bias voltage to form a second component layer, and the temperature is reduced to obtain the nanostructured coating.

[0047] Preferably, the process temperature is 450°C-650°C, for example, 450°C, 500°C, 550°C, 600°C or 650°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0048] Preferably, the negative bias voltage is -30V to -150V, for example, -30V, -50V, -80V, -100V, -120V or -150V, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0049] Preferably, the reaction gas includes any one of nitrogen, oxygen or acetylene or a combination of at least two of them, wherein nitrogen, oxygen or acetylene respectively provide nitrogen, oxygen and carbon elements in the physical vapor deposition process.

[0050] When only argon gas is introduced during the physical vapor deposition process, the argon gas serves to maintain the existence of the arc, glow or plasma and does not participate in the elemental reaction of the deposition.

[0051] Preferably, during the physical vapor deposition process, the relative evaporation and ionization rates of the target elements can be controlled by controlling the target currents of the first component target and the second component target, thereby controlling the deposition rates of the first component and the second component on the substrate surface, and further controlling the thicknesses of the first component layer and the second component layer, respectively.

[0052] Optionally, the target current ranges from 140A to 230A, for example, 140A, 150A, 160A, 180A, 200A, 210A or 230A, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0053] The baffle between the first component target and the rotating disk is the first baffle, and the baffle between the second component target and the rotating disk is the second baffle. When the first baffle is opened to the maximum, the second baffle is opened to the minimum but not closed. At this time, the rotating disk rotates one or more times to obtain at least one composite structure layer with the first component layer having the largest thickness and the second component layer having the smallest thickness. On the contrary, when the second baffle is opened to the maximum, the first baffle is opened to the minimum but not closed. At this time, the rotating disk rotates one or more times to obtain at least one composite structure layer with the second component layer having the largest thickness and the first component layer having the smallest thickness. Therefore, by setting the appropriate rotating disk speed and baffle opening and closing cycle, the first component layer and the second component layer of the desired thickness and thickness correlation can be obtained.

[0054] In the present invention, the time that the surface to be coated of the substrate stays in front of different metal targets can be controlled by adjusting the rotation speed of the rotating disk, thereby controlling the deposition thickness; optionally, the quantitative relationship between the first component target and the second component target can be appropriately adjusted to change the relative thickness of the first component layer and the second component layer.

[0055] Preferably, during the physical vapor deposition, the rotation speed of the rotating disk is T1 r / min, the opening and closing frequency of the baffle is T2 times / min, then T1 is an integer multiple of T2, and the multiple of the integer multiple is the same as the number of composite structure layers in the periodic coating unit.

[0056] Preferably, the substrate is pretreated before physical vapor deposition to obtain a coating surface that is conducive to coating deposition and adhesion.

[0057] Optionally, the pretreatment method includes any one of machining, sandblasting, demagnetization or cleaning, or a combination of at least two of them.

[0058] Optionally, the mechanical processing includes: processing the substrate to a desired workpiece shape and size through grinding, polishing and other processes, and smoothing the polished surface to improve the bonding strength between the coating and the substrate.

[0059] Optionally, the sandblasting includes: passivating the overly sharp and uneven edges of the substrate surface to be coated by dry or wet blasting, reducing the internal stress of the coating film on the edges, reducing crack generation and coating peeling, smoothing the surface to be coated, and reducing surface scratches to facilitate coating deposition.

[0060] Optionally, the demagnetization includes: removing the magnetism of the substrate itself by applying a certain changing magnetic field, reducing the adhesion of magnetic dust on the surface of the substrate to be coated, reducing the influence of the substrate magnetism on the electric field magnetic distribution in the furnace, and improving the bonding strength of the nanostructured coating and the stability of the coating uniformity.

[0061] Optionally, the cleaning includes: using pure water, alkaline cleaning agent, ultrasound, high-temperature drying and other methods to clean the dirt and dust on the surface of the substrate to be coated, which is beneficial to the deposition and adhesion of the nanostructured coating and improves the bonding strength.

[0062] In a third aspect, the present invention provides a cutting tool, comprising the nanostructured coating described in the first aspect.

[0063] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0064] Compared with the prior art, the present invention has the following beneficial effects:

[0065] The nanostructured coating provided by the present invention has both ultra-hardness in thin periods and toughness in thick periods through specific periodic coating units. When applied to cutting tools, the service life of the cutting tools can be significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 This is a schematic diagram of the structure of the double-periodic nanostructured coating provided in Example 1 of the present invention.

[0067] Figure 2 It is a top view of the structure of the physical vapor deposition device in a specific embodiment of the present invention, and the arrows in the figure indicate the opening and closing directions of the baffles.

[0068] Among them: 1, first component layer; 2, second component layer; 3, composite structure layer; 4, periodic coating unit; 5, first component target; 6, second component target; 7, first baffle; 8, second baffle; 9, rotating disk. DETAILED DESCRIPTION

[0069] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0070] In a specific embodiment of the present invention, a WC-based cemented carbide blade is used as a substrate, wherein the Co content is 10wt%, the VC content is 0.2wt% and the balance is WC. The average particle size of WC, Co and VC is 0.8μm, and the blade model is WNMG080408-LM. The WC-based cemented carbide blade is pretreated before use, specifically: the surface of the WC-based cemented carbide blade is mechanically flat ground; a double-end face grinder equipped with a 600-mesh diamond grinding wheel is used for polishing to obtain a flat and smooth blade surface to be attached, and the blade tip clamping height is 4±0.01mm; a mixed liquid with Al2O3 powder is sprayed with a high-pressure water gun to passivate the blade edge radius to 30μm; the blade is ultrasonically cleaned with high-purity water, and then dried at high temperature, and then a double-period nanostructure coating is set using the method in the following embodiment and comparative example.

[0071] The physical vapor deposition apparatus for the following embodiments and comparative examples is as follows: Figure 2 The device shown includes: a rotating disk 9, which is used to fix the substrate; the first component target 5 and the second component target 6 are evenly placed around the rotating disk; the sputtering surface of the first component target 5 and the sputtering surface of the second component target 6 are respectively facing the surface to be coated of the substrate, and baffles capable of controlling the opening and closing size are independently arranged between the first component target 5 and the rotating disk 9, and between the second component target 6 and the rotating disk 9. The baffle between the first component target 5 and the rotating disk 9 is the first baffle 7, and the baffle between the second component target 6 and the rotating disk 9 is the second baffle 8. When the first baffle 7 is opened to the maximum, the second baffle 8 is opened to the minimum but not closed. At this time, after the rotating disk 9 rotates one circle, the first component layer with the thickest thickness and the second component layer with the thinnest thickness are obtained; conversely, when the second baffle 8 is opened to the maximum, the first baffle 7 is opened to the minimum but not closed. After the rotating disk 9 rotates one circle, the first component layer with the thinnest thickness and the second component layer with the thickest thickness are obtained.

[0072] The physical vapor deposition using the device comprises: fixing a substrate on a rotating disk, heating to a process temperature under vacuum conditions, introducing argon gas for etching, and then introducing argon gas and / or reaction gas for coating deposition; when the surface to be coated of the substrate faces a first component target material, atoms on the surface of the first target material are ionized under the action of high temperature and electric arc, and ions move toward the surface to be coated of the substrate under the action of negative bias voltage to form a first component layer; when the surface to be coated of the substrate faces a second component target material, atoms on the surface of the second target material are ionized under the action of high temperature and electric arc, and ions move toward the surface to be coated of the substrate under the action of negative bias voltage to form a second component layer, and cooling is performed to obtain the double-periodic nanostructure coating.

[0073] The testing method in the specific implementation manner of the present invention includes:

[0074] (I) A transmission electron microscope (TEM) is used for measurement, and the magnification of the TEM is set to 1.25 million times. A first component layer and a second component layer with different light and dark stripes can be clearly observed in the field of view. The first component layer and the second component layer are analyzed by the EDS module of the TEM equipment to obtain the atomic ratio content of each element in the coating. Five measurement points are selected and the average value is taken as the composition of each layer of the coating. Under the field of view of 1.25 million times, five areas are selected for photography. The thickness of the first component layer and the second component layer in each figure is measured according to the ruler and the average value is taken as the single layer thickness of each layer of the coating.

[0075] (II) The coating hardness was measured using a nanoindenter, Anton-Paar TriTec UNHT3, with a maximum load of 20 mN, a loading and unloading time of 30 s, and a holding time of 5 s. The instrument measured the relationship between the loading force and the indentation depth, and automatically calculated the hardness (GPa) of the coating. The measurement was repeated 16 times in a 4×4 matrix mode, and the curves and values ​​with excessive deviations were deleted, and the average value was taken as the hardness at room temperature.

[0076] (III) Using TRIBO Millennium 200 scratch tester to measure the strength of the coating adhesion: using a conical diamond indenter with a smooth tip to scratch the coating surface at a certain speed, while gradually increasing the vertical pressure of the indenter, the minimum pressure of the coating cracking is used to characterize the strength of the coating film-based adhesion; the measurement parameters are: scratch length of 12mm, scratch speed of 5mm / min, indenter pressure of 0N-120N, loading speed of 50N / min. According to the acoustic signal of coating cracking collected synchronously in the scratch loading test, the change of friction force of the indenter scratching the substrate, the cracking of the coating surface and the pressure corresponding to its position, etc., the critical load force when the coating cracks is determined, and the average of the three measurements is the coating film-based adhesion described in the present invention.

[0077] (IV) Cutting test of 304 stainless steel: the base hardness of 304 stainless steel is 220HB, the cutting speed is 180m / min, the feed rate is 0.2mm / r, the cutting depth is 2mm, and coolant is used for water cooling during the cutting process; the cutting is paused for 1min every time to observe whether the blade is chipped or the flank wear value exceeds 0.3mm; cutting is continued until the blade is chipped or the flank wear exceeds 0.3mm, which is the cutting life of the blade; each group of tests is conducted 3 times, and the average value is taken as the corresponding cutting life.

[0078] Example 1

[0079] This embodiment provides a Figure 1The nanostructured coating shown includes periodic coating units 4 stacked in sequence; the periodic coating units 4 include four composite structure layers 3 ; the composite structure layers include a first component layer 1 and a second component layer 2 .

[0080] The preparation method of the nanostructured coating comprises:

[0081] (1) The substrate is clamped on a rotating disk of a physical vapor deposition device (arc ion plating equipment furnace), and a first component target 5 and a second component target 6 are evenly placed on the circumference of the rotating disk. The number ratio of the first component target 5 to the second component target 6 is 1:1; the first component of the first component target 5 is Ti 0.35 Al 0.55 Nb 0.1 The second component of the second component target 6 is Ti 0.35 Al 0.65 ;

[0082] The rotating disk speed was set to 2 r / min, and the arc ion plating equipment furnace was evacuated to 5 × 10 -4 mbar, and the substrate surface is heated to 500°C and kept stable by the heating device in the furnace of the arc ion plating equipment; Ar gas is introduced into the furnace of the arc ion plating equipment to maintain the Ar partial pressure in the furnace at 0.05mbar to maintain the generation of the metal target arc, and the Ar ionization chamber switch is turned on, and the negative bias voltage is set to -200V, so that the ionized Ar ions bombard the blade substrate at a high speed under the action of the electric field, and the etching is continued for 30 minutes.

[0083] (2) Maintaining the Ar partial pressure unchanged, the reaction gas N2 is introduced for coating deposition, wherein the N2 gas partial pressure is 0.05 mbar; the deposition negative bias voltage is set to -60 V, the arc evaporation device of the first component target 5 and the second component target 6 is started, and the target current of the first component target 5 is set to 180 A, and the target current of the second component target 6 is set to 180 A; during the deposition process, as the rotating disk 9 rotates, when the surface to be coated of the substrate faces the first component target 5, the atoms of the first component target are ionized under the action of high temperature and arc, and the ions move toward the surface to be coated of the substrate under the action of negative bias, and react and deposit into the first component layer 1; when the surface to be coated of the substrate faces the second component target 6, the atoms of the second component target are also reacted and deposited into the second component layer 2; at the same time, the opening and closing frequency of the baffle is set to be 1 time for every 4 rotations of the rotating disk. When the first baffle 7 is opened to the maximum of 100%, the opening amplitude of the second baffle 8 is set to 50%, and the rotating disk 9 rotates for two weeks to obtain two layers of composite structure layer 3, wherein the thickness of the first component layer 1 is greater than the thickness of the second component layer 2; after the rotating disk 9 rotates for two weeks, the baffle state is switched, and when the second baffle 8 is opened to the maximum of 100%, the opening amplitude of the first baffle 7 is set to 50%, and the rotating disk 9 rotates for two weeks to obtain two layers of composite structure layer 3, wherein the thickness of the first component layer 1 is less than the thickness of the second component layer 2, and each 4 rotations of the rotating disk 9 constitute a periodic coating unit 4. Keep the rotating disk 9 rotating continuously, the baffles are opened and closed periodically, and the periodic precipitation is carried out for 60 minutes to obtain a nanostructured coating.

[0084] (3) After stopping the deposition, Ar gas is introduced to maintain the pressure in the furnace at 200 mbar, and the fan in the furnace is turned on. The coating furnace is cooled rapidly. When the temperature is cooled to 100° C., the coating furnace is taken out of the furnace to obtain the following Figure 1 Nanostructured coating shown.

[0085] The first target material, the second target material, the rotating disk speed, the number of rotations (R) of a periodic coating unit, the minimum opening amplitude of the baffle, the target current of the first target material, the target current of the second target material and the reaction atmosphere gas used in Example 2-Example 17 and Comparative Example 1-Comparative Example 3 are shown in Table 1 and Table 2; in Example 4 and Example 5, each 3 rotations of the rotating disk constitute a periodic coating unit, and the baffles are set as follows: when the first baffle is opened to a maximum of 100%, the opening amplitude of the second baffle is 50%, and the rotating disk rotates one circle to deposit the thickest first component layer and the thinnest second component layer; then, when the first baffle is opened to 75% and the second baffle is opened to 75%, the rotating disk rotates one circle to deposit the first component layer and the second component layer of similar thickness; then, when the first baffle is opened to 50%, the opening amplitude of the second baffle is 100%, and the rotating disk rotates one circle to deposit the thinnest first component layer and the thickest second component layer.

[0086] In Example 6 and Example 7, every 10 rotations of the rotating disk constitute a periodic coating unit, and the baffle settings are as follows: the first baffle is opened to a maximum of 100%, the opening amplitude of the second baffle is 50%, and the rotating disk rotates 5 times to deposit 5 layers of a composite structure layer having a first component layer with the thickest thickness and a second component layer with the thinnest thickness; subsequently, the first baffle is opened to 50%, the opening amplitude of the second baffle is 100%, and the rotating disk rotates 5 times to deposit 5 layers of a composite structure layer having a second component layer with the thickest thickness and a first component layer with the thinnest thickness.

[0087] In Example 17, every 11 rotations of the rotating disk is a periodic coating unit, and the baffles are set as follows: the first baffle is opened to a maximum of 100%, the opening amplitude of the second baffle is 50%, and the rotating disk rotates 5 times to deposit 5 layers of a composite structure layer having a first component layer with the thickest thickness and a second component layer with the thinnest thickness; then when the first baffle is opened to 75% and the second baffle is opened to 75%, the rotating disk rotates 1 circle to deposit a first component layer and a second component layer with similar thickness; then, the first baffle is opened to 50%, the opening amplitude of the second baffle is 100%, and the rotating disk rotates 5 circles to deposit 5 layers of a composite structure layer having a second component layer with the thickest thickness and a first component layer with the thinnest thickness.

[0088] The compositions of the first component and the second component in the obtained nanostructured coating are shown in Table 3; the thickness of each layer is shown in Table 4, and the relationship between the thickness of each layer is shown in Table 5. The thickness of the thickest first component layer is a max The thickness of the thinnest first component layer is a min The thickness of the second component layer is b. max The thickness of the thinnest second component layer is b min The thickness of the thickest composite structure layer is c max , the thickness of the thinnest composite structure layer is c min , the thickness of the periodic coating unit is d, and the unit of the thickness of each layer is nm; the test results of room temperature hardness, bonding strength and cutting life are shown in Table 6. The qualified value of room temperature hardness should be greater than 30GPa, the bonding strength should be greater than 60N, and the cutting life should be greater than 20min.

[0089] Table 1

[0090]

[0091]

[0092] Table 2

[0093]

[0094]

[0095] Table 3

[0096] First ingredient Second ingredient Example 1 <![CDATA[Ti 0.38 Al 0.52 Nb 0.1 N 0.99 ]]> <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.38 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.62 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.01 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> Example 2 <![CDATA[MoN 0.98 ]]> <h2 style=";text-align:left;direction:ltr"><![CDATA[Zr <h2 style=";text-align:left;direction:ltr"> 0.47 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.44 <h2 style=";text-align:left;direction:ltr"> W<h2 style=";text-align:left;direction:ltr"> 0.09 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.01 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> Example 3 <h2 style=";text-align:left;direction:ltr"><![CDATA[Cr <h2 style=";text-align:left;direction:ltr"> 0.42 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.58 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.00 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> <![CDATA[Ti 0.83 Yes 0.17 N 1.00 ]]> Example 4 <h2 style=";text-align:left;direction:ltr"><![CDATA[Hf <h2 style=";text-align:left;direction:ltr"> 0.52 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.38 <h2 style=";text-align:left;direction:ltr"> V<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.01 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> <![CDATA[W 0.84 I 0.16 N 0.99 ]]> Example 5 <h2 style=";text-align:left;direction:ltr"><![CDATA[Hf <h2 style=";text-align:left;direction:ltr"> 0.52 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.39 <h2 style=";text-align:left;direction:ltr"> V<h2 style=";text-align:left;direction:ltr"> 0.09 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 0.98 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> <![CDATA[W 0.83 I 0.17 N 0.98 ]]> Example 6 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.37 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.53 <h2 style=";text-align:left;direction:ltr"> Zr<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.02 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.37 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.53 <h2 style=";text-align:left;direction:ltr"> Hf<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.00 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> Example 7 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.38 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.52 <h2 style=";text-align:left;direction:ltr"> Zr<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.00 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.37 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.53 <h2 style=";text-align:left;direction:ltr"> Hf<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.01 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> Example 8 TiC WC Example 9 <![CDATA[AlO 1.5 ]]> <![CDATA[CrO 1.5 ]]> Example 10 <![CDATA[TiB2]]> <![CDATA[ZrB2]]> Embodiment 11 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.31 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.59 <h2 style=";text-align:left;direction:ltr"> Ta<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 0.99 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.31 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.69 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.00 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> Example 12 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.59 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.31 <h2 style=";text-align:left;direction:ltr"> Ta<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 0.98 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.49 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.31 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.01 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> Example 13 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.38 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.43 <h2 style=";text-align:left;direction:ltr"> Ta<h2 style=";text-align:left;direction:ltr"> 0.19 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.02 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.38 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.62 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 0.99 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> Embodiment 14 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.29 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.61 <h2 style=";text-align:left;direction:ltr"> Ta<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.00 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.29 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.71 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.01 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> Embodiment 15 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.61 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.29 <h2 style=";text-align:left;direction:ltr"> Ta<h2 style=";text-align:left;direction:ltr"> 0.1 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 0.99 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.71 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.29 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.00 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> Example 16 <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.38 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.41 <h2 style=";text-align:left;direction:ltr"> Ta<h2 style=";text-align:left;direction:ltr"> 0.21 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.00 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.38 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.62 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 0.98 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> Embodiment 17 <![CDATA[Ti 0.38 Al 0.52 Nb 0.1 N 1.00 ]]> <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.38 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.62 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.00 <h2 style=";text-align:left;direction:ltr"><!-- 10 --> ]]><h2 style=";text-align:left;direction:ltr"> Comparative Example 1 <![CDATA[Ti 0.38 Al 0.52 Nb 0.1 N 0.98 ]]> <h2 style=";text-align:left;direction:ltr"><![CDATA[Ti <h2 style=";text-align:left;direction:ltr"> 0.38 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.62 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.02 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> Comparative Example 2 <![CDATA[MoN 0.97 ]]> <h2 style=";text-align:left;direction:ltr"><![CDATA[Zr <h2 style=";text-align:left;direction:ltr"> 0.47 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.44 <h2 style=";text-align:left;direction:ltr"> W<h2 style=";text-align:left;direction:ltr"> 0.09 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.02 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> Comparative Example 3 <h2 style=";text-align:left;direction:ltr"><![CDATA[Cr <h2 style=";text-align:left;direction:ltr"> 0.42 <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> 0.58 <h2 style=";text-align:left;direction:ltr"> N<h2 style=";text-align:left;direction:ltr"> 1.01 <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> <![CDATA[Ti 0.83 Yes 0.17 N 0.98 ]]>

[0097] Table 4

[0098]

[0099] Table 5

[0100]

[0101]

[0102] Table 6

[0103] Room temperature hardness (GPa) Binding force (N) Cutting life (min) Example 1 34.1 63 23.3 Example 2 30.3 63 20.6 Example 3 34.6 62 20.7 Example 4 35.1 63 21.0 Example 5 35.4 62 20.3 Example 6 30.5 64 21.0 Example 7 30.3 66 20.7 Example 8 31.5 62 21.3 Example 9 33.0 62 21.0 Example 10 33.8 65 23.7 Embodiment 11 32.1 64 22.7 Example 12 31.3 62 21.7 Example 13 32.1 63 23.0 Embodiment 14 32.4 62 21.3 Embodiment 15 30.2 61 20.3 Example 16 31.7 61 21.7 Embodiment 17 32.3 60 20.3 Comparative Example 1 29.4 65 18.7 Comparative Example 2 28.8 62 18.3 Comparative Example 3 34.7 59 18.3

[0104] From Table 1 to Table 6, we can see that:

[0105] (1) Example 1 is the nanostructured coating of the present invention, the baffle width is 50%, due to the shielding of the baffle, the single layer thickness a min With b min Thickness compared to a max and b max To be thin, so that its thickness relationship satisfies the relationship: 1.5≤a max / a min ≤3, 1.5≤b max / b min ≤3,1.5≤a max / b min ≤3, 1.5≤b max / a min ≤3. Comparative Example 1 is an existing single-cycle nanostructured coating. During the coating process, the baffle is always in a 100% open state, and the baffle has no effect on the coating deposition. max 、a min , b max , b min The thickness of each layer is similar, and the thickness relationship is not satisfied. min With b min The thickness of a single layer is only half of that of comparative example 1. When other conditions remain unchanged, its nano-superhard effect is greatly improved, and the overall hardness of the coating is significantly improved. Under the premise of qualified bonding strength and no chipping, the cutting life of the blade is comprehensively improved. Comparative example 1 has an unqualified hardness, a low overall cutting life, and does not meet the performance requirements.

[0106] (2) Both Example 2 and Comparative Example 2 are nanostructured coatings, but the baffle widths of the two are different, which makes the coating structures of the two different. The single layer thickness of Example 2 satisfies the relationship: a max / a min ≥1.5, bmax / b min ≥1.5, a max / b min ≥1.5, b max / a min ≥1.5; the single layer thickness of comparative example 2 is: a max / a min <1.5, b max / b min <1.5, a max / b min <1.5, b max / a min <1.5. Compared with Example 2, the thickness difference between each single layer of the coating of Comparative Example 2 is smaller, the superhard effect of the thin single layer cannot be significantly improved, and the overall thickness is thicker. Therefore, its overall hardness, wear resistance and cutting life are worse than those of Example 2 and do not meet the performance requirements.

[0107] (3) Both Example 3 and Comparative Example 3 are nanostructured coatings, but the baffle widths of the two are different, which makes the coating structures of the two different. The single layer thickness of Example 3 satisfies the relationship: a max / a min ≤3, b max / b min ≤3, a max / b min ≤3, b max / a min ≤3; the single layer thickness of comparative example 3 is: a max / a min >3,b max / b min >3,a max / b min >3,b max / a min >3. Compared with Example 3, the thickness difference between the individual layers of the coating in Comparative Example 3 is larger, a min With b min If the thickness is too small, the microstructures such as the phase composition and lattice constant of the thinner second component layer will tend to grow epitaxially on the basis of the thicker first component layer, causing the thinner second component layer to undergo lattice distortion, from the lattice constant of the second component to the lattice constant of the first component. Although this will increase the hardness of the coating, it will also cause the coating's resistance to plastic deformation to decline, thereby reducing the coating's bonding strength. This makes the bonding strength and overall cutting life of Comparative Example 3 lower than those of Example 3, and does not meet the performance requirements.

[0108] (4) In the first component layer and the second component thick layer of Example 4, each layer has a thickness greater than 4 nm, and c min >12nm, d>36nm. a of Example 5min With b min Less than 4nm, and c min <12nm, d<36nm, too small a min and b min , due to the tendency of epitaxial growth, it brings about excessive lattice distortion; too small c min and d, so that the number and density of nano-coating interfaces increase. These all reduce the bonding strength of the coating, making the bonding strength and overall cutting life of Example 5 lower than that of Example 4, but still meeting the performance requirements.

[0109] (5) In the first component layer and the second component layer of Example 6, each layer has a thickness less than 70 nm, and c max <100nm, d<1000nm. a of Example 7 max With b max Greater than 70nm, and c max >100nm, d>1000nm. Too thick nanolayer makes the nano superhard effect insignificant, and the overall hardness of the coating decreases, so that the hardness and overall cutting life of Example 7 are lower than those of Example 6, but still meet the performance requirements.

[0110] (6) In Example 8, the gas introduced is acetylene, which reacts with the target ions to deposit a carbide coating; in Example 9, the gas introduced is oxygen, which reacts with the target ions to deposit an oxide coating; in Example 10, the gas introduced is argon, which is used to maintain the arc and does not react with the target ions to deposit a boride coating. The thickness of each nano single layer in each embodiment satisfies the thickness relationship, and the overall hardness, bonding strength, and cutting life of the coating are all qualified.

[0111] (7) The contents of the coating components M1 and N1 (both are Ti) in Example 11 are greater than 0.3; the contents of the coating components M1 and N1 (both are Ti) in Example 14 are less than 0.3, which results in insufficient Ti content in the main phase (i.e., TiN phase) of each layer in Example 14, and the coating cannot form a complete cubic TiAlN main phase structure, resulting in the precipitation of some impurity phases such as hexagonal AlN phase. The precipitated phase has a lower hardness than the main phase, and at the same time destroys the coating structure and reduces the coating bonding strength, so that the overall hardness, bonding strength, and cutting life of Example 14 are lower than those of Example 11, but still meet the performance requirements.

[0112] (8) The contents of the coating components M2 and N2 (both Al) in Example 12 are greater than 0.3; the contents of the coating components M2 and N2 (both Al) in Example 15 are less than 0.3. This makes the relative content of Al in each layer of Example 15 too low, and the coating cannot be fully alloyed and strengthened, so that the overall hardness, bonding strength, and cutting life of Example 15 are lower than those of Example 12, but still meet the performance requirements.

[0113] (9) The coating components M3 and N3 (both Ta) in Example 13 have a content of <0.2; the coating component M3 (Ta) in Example 16 has a content of >0.2, which causes the layers of Example 16 to dissolve excessive Ta, thereby precipitating a portion of TaN phase in the TiAlN cubic phase. The precipitated phase has a lower hardness than the main phase, and at the same time destroys the coating structure and reduces the coating bonding force, so that the overall hardness, bonding force, and cutting life of Example 16 are all lower than those of Example 13, but still meet the performance requirements.

[0114] (10) Compared with Example 1, more composite structural layers appear in a single periodic coating unit of Example 17 coating. The continuous composite structural layers with a thickness of multiple first component layers greater than the thickness of the second component layers make the microstructures such as the phase components and lattice constants of these second component layers more inclined to epitaxially grow on the basis of the first component layers, causing the second component layers to undergo lattice distortion, from the lattice constant of the second component to the lattice constant of the first component. Similarly, the continuous composite structural layers with a thickness of multiple first component layers less than the thickness of the second component layers make the microstructures such as the phase components and lattice constants of these first component layers more inclined to epitaxially grow on the basis of the second component layers, causing the first component layers to undergo lattice distortion, from the lattice constant of the first component to the lattice constant of the second component. Although this will increase the hardness of the coating, it will also cause the coating's resistance to plastic deformation to decline, thereby reducing the coating's bonding strength, which makes the bonding strength and overall cutting life of Example 17 lower, but still meets the performance requirements.

[0115] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A nanostructured coating, characterized in that: The nanostructured coating comprises periodic coating units stacked in sequence; The periodic coating unit includes at least 3 composite structure layers; The composite structure layer comprises a first component layer and a second component layer; in at least one composite structure layer, the thickness of the first component layer is greater than the thickness of the second component layer; in at least one composite structure layer, the thickness of the second component layer is greater than the thickness of the first component layer; In each of the composite structure layers of a single periodic coating unit, the thickness of the first component layer is completely different or not completely the same, and the thickness of the second component layer is completely different or not completely the same; In the periodic coating unit, the thickness of the thickest first component layer is a max The thickness of the thinnest first component layer is a min The thickness of the second component layer is b. max The thickness of the thinnest second component layer is b min , the unit of thickness of each layer is nm; In the periodic coating unit, the thickness of each layer satisfies: 1.5≤a max / a min ≤3, 1.5≤b max / b min ≤3,1.5≤a max / b min ≤3, 1.5≤b max / a min ≤3.

2. The nanostructured coating according to claim 1, characterized in that: The periodic coating unit includes 3 to 10 composite structure layers.

3. The nanostructured coating according to claim 1 or 2, characterized in that: The thickness of the first component layer is 4nm-70nm; And / or, the thickness of the second component layer is 4nm-70nm.

4. The nanostructured coating according to claim 3, characterized in that: The thickness of the composite structure layer is 12nm-100nm; And / or, the thickness of the periodic coating unit is 36nm-1000nm.

5. The nanostructured coating according to claim 1, characterized in that: The first component in the first component layer is M1 a M2 b M3 c M m , M1 includes any one of Ti, Cr, Zr, Hf, W or Mo, M2 includes Al, M3 includes any one of Ti, Cr, Zr, Hf, V, Ta, Nb, W, Mn, Mo or Si or a combination of at least two, M is any one of N, O, C or B or a combination of at least two; and a>0.3, b>0.3 or b=0, c≤0.2, and a+b+c=1; When M is N and / or C, 0.95≤m≤1.05; when M is O, 1.45≤m≤1.55; when M is B, 1.95≤m≤2.

05.

6. The nanostructured coating according to claim 1, characterized in that: The second component in the second component layer is N1 x N2 y N3 z Q q , N1 includes any one of Ti, Cr, Zr, Hf, W or Mo, N2 includes Al, N3 includes any one of Ti, Cr, Zr, Hf, V, Ta, Nb, W, Mn, Mo or Si or a combination of at least two, Q is any one of N, O, C or B or a combination of at least two; and x>0.3, y>0.3 or y=0, z≤0.2, and x+y+z=1; When Q is N and / or C, 0.95≤q≤1.05; when Q is O, 1.45≤q≤1.55; when Q is B, 1.95≤q≤2.

05.

7. A method for preparing a nanostructured coating, characterized in that: The preparation method comprises the following steps: The periodic coating units are sequentially deposited on the surface of the substrate by a physical vapor deposition method to obtain the nanostructured coating according to any one of claims 1 to 6.

8. The preparation method according to claim 7, characterized in that: The physical vapor deposition device used in the physical vapor deposition comprises: A rotating disk, the rotating disk is used to fix the substrate; The first component target and the second component target are evenly placed around the rotating disk; the sputtering surface of the first component target and the sputtering surface of the second component target are respectively facing the surface to be coated of the substrate, and baffles capable of controlling the opening and closing size are independently arranged between the first component target and the rotating disk and between the second component target and the rotating disk.

9. The preparation method according to claim 8, characterized in that: During the physical vapor deposition, the rotation speed of the rotating disk is T1 r / min, and the opening and closing frequency of the baffle is T2 times / min, then T1 is an integer multiple of T2, and the multiple of the integer multiple is the same as the number of composite structure layers in the periodic coating unit.

10. A cutting tool, characterized in that: The cutting tool comprises the nanostructured coating according to any one of claims 1-6.